LEXICAL PROBLEMS OF TRANSLATION - Akhnazarov Abdulazizbek Boyxo’roz o’g’li; Zilola Abdurakhmanova Yoqubjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Translation is a delicate dance of conveying not just the words but the nuances, cultural contexts, and shades of meaning from one language to another. At the heart of this intricate process lie lexical challenges, where the choices of words can significantly impact the fidelity and effectiveness of the translated text. This article explores the complexities of lexical problems in translation, shedding light on the subtleties that translators must navigate to ensure a faithful and resonant rendition.